2007
DOI: 10.1080/10810730701672520
|View full text |Cite
|
Sign up to set email alerts
|

Messages From Moms: Barriers to and Facilitators of Behavior Change in a Lead Poisoning Preventive Education Project

Abstract: Qualitative focus group data from participants of an intensive, culture-specific, lead poisoning preventive education research project were analyzed to assess success of communication strategies, and, specifically, to identify barriers to and facilitators of adopting behavior changes encouraged in the project. Effectiveness of education in preventing lead poisoning is addressed elsewhere. Education focused on housecleaning, hygiene, water, and nutrition. Ninety-five participants (89% of 107 eligible) of six et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Post hoc, social cognitive theory provided a framework for examining the responses of focus group participants to the mobile video show . Social cognitive theory posits a structure in which self‐efficacy beliefs operate in concert with goals, outcome expectations, and perceived environmental impediments and facilitators to regulate human motivation, action, health habits, and overall well‐being .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post hoc, social cognitive theory provided a framework for examining the responses of focus group participants to the mobile video show . Social cognitive theory posits a structure in which self‐efficacy beliefs operate in concert with goals, outcome expectations, and perceived environmental impediments and facilitators to regulate human motivation, action, health habits, and overall well‐being .…”
Section: Discussionmentioning
confidence: 99%
“…They can employ a number of media (eg, print, broadcast, video) to convey their message. Numerous observational studies, a typical evaluation strategy, 5‐7 have shown credible associations between changes in behavior and exposure to behavior change communication 8‐10 . A number of theoretical frameworks undergird behavior change communication efforts.…”
Section: Introductionmentioning
confidence: 99%
“…The novelty of the concept of lead, combined with the threat of the adverse impacts of lead exposure, may explain the interest with which women participated in the intervention and the notable improvements in knowledge and behavior. A household-level lead prevention intervention in the US noted that women were more responsive if they had never heard about the issue before ( Jordan et al, 2007 ). CHWs made the concept of lead itself relatable by comparing it to arsenic, a familiar invisible toxin.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, individuals, and families with children, at risk of lead poisoning need individualized interventions that place an emphasis on lead poisoning diagnosis, testing, and prevention incorporated into their existing lifestyles. In a study by Jordan et al an already burdened family was more likely to adopt practices and behaviors that were easy to implement and did not add any steps to their daily routine [32]. Systematic and organizational level approaches might be more suitable to mitigate lead poisoning by developing collaborations, creating one-stop-shops for lead-related services, or streamlining processes to minimize steps and efforts to address lead poisoning.…”
Section: Discussionmentioning
confidence: 99%